Inovasi dan Kreativitas Sebagai Kunci Keberhasilan Wirausaha di Era Digital - Caca Ramadani; Alfiya Nur Khasanah; Yulia Novita (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2025)
The advancement of digital technology has brought significant changes to various aspects of life, including entrepreneurial activities. In the digital era, characterized by rapid developments in information and communication technologies, the ability of entrepreneurs to innovate and create has become a key factor in determining business success. This study aims to analyze the crucial role of innovation and creativity in helping business owners face increasingly intense global competition. The research employs a qualitative descriptive method through a literature review from various scholarly sources. The findings show that innovation and creativity greatly influence the creation of competitive advantage, improvements in operational efficiency, and the ability to adapt to shifts in consumer behavior. Entrepreneurs who can integrate creative ideas with technological applications have greater opportunities to grow and sustain their businesses in the digital marketplace. The study also highlights several challenges in fostering creativity and innovation, particularly amid rapid technological changes and evolving consumer preferences